Analysis of actuator in-phase property in terms of control performance and integrated plant/controller design using a novel model matching method - Du, Chunling (2013)
This paper is concerned with resonance in-phase property of a VCM (voice coil motor) plant system in the sense of control performance in HDDs (hard disk drives). Its relationships with the optimal performance level γopt, the stability margins and the disturbance rejection capability are revealed. It is found that the main resonance being in-phase is particularly beneficial to rejection of the narrow-band disturbances with frequencies near plant resonances. In order to meet the requirement on the inphase property, a partial model matching method is proposed. This model matching problem is solved by an H∞ method using an linear matrix inequality approach. The partial model matching method is then applied to the VCM plant system. We especially take into account the in-phase case for the purpose to improve the system ability to attenuate high frequency disturbance. For the new system designed using the proposed model matching method, a feedback controller and a group peak filter are designed to attenuate the disturbance near the plant resonances. The advantages of the in-phase resonances are illustrated, when compared with the original plant.